Unusual Case of Malignant Struma Ovarii and Cervical Thyroid Cancer Preceded by Ovarian Teratoma: Case Report and Review of the Literature - Elias G. Tzelepis; Elena Barengolts; Steven Garzon; Joseph Shulan; Yuval Eisenberg (Case Reports in Endocrinology)
Objective. To present a rare case of malignant struma ovarii (MSO) and synchronous thyroid cancer, review the medical literature, and present the latest trends in management. Methods. The case of a woman with MSO and concomitant thyroid cancer is presented, including clinical presentation, treatment, and follow-up care. A search of the English-language literature was conducted using MEDLINE and Google Scholar data bases. Results. We found 10 publications (one abstract) describing 10 patients with MSO and concomitant thyroid cancer. Six additional patients were reported by a study that analyzed the SEER (cancer registry) database. The median age of women was 42 years, with the majority of them presenting with abdominal symptoms. Histologically, most tumors were papillary carcinomas in both organs. In 5 patients, there was extrathyroidal tumor extension at time of surgery. Conclusion. MSO can occasionally coexist with highly aggressive eutopic thyroid cancer. Although this concurrence is even rarer than MSO, clinicians should routinely investigate for possible synchronous thyroid cancer in all cases of MSO and also consider aggressive postoperative treatment including thyroidectomy and radioiodine ablation therapy in cases of MSO.